2022
DOI: 10.1029/2021gl096994
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Set of Juno In Situ and Remote Sensing Observations of the Ganymede Auroral Footprint

Abstract: Jupiter's satellite auroral footprints are a manifestation of the satellite‐magnetosphere interaction of the Galilean moons. Juno's polar elliptical orbit enables crossing the magnetic flux tubes connecting each Galilean moon with their associated auroral emission. Its payload allows measuring the fields and particle population in the flux tubes while remotely sensing their associated auroral emissions. During its thirtieth perijove, Juno crossed the flux tube directly connected to Ganymede's leading footprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 65 publications
(98 reference statements)
5
25
0
Order By: Relevance
“…A multi‐event study of the Io‐magnetosphere interaction based on Juno data has revealed that the precipitating electron energy flux (EF) decreases exponentially with distance in the footprint tail (Szalay et al., 2020b). These measurements are consistent with the observed variation of the UV brightness of the Io auroral tail (Bonfond, Saur, et al., 2017; Hue et al., 2022).…”
Section: Introductionsupporting
confidence: 90%
“…A multi‐event study of the Io‐magnetosphere interaction based on Juno data has revealed that the precipitating electron energy flux (EF) decreases exponentially with distance in the footprint tail (Szalay et al., 2020b). These measurements are consistent with the observed variation of the UV brightness of the Io auroral tail (Bonfond, Saur, et al., 2017; Hue et al., 2022).…”
Section: Introductionsupporting
confidence: 90%
“…Alfvénic acceleration processes were also observed when crossing the fluxtube connected to Ganymede's footprint tail (Szalay, Allegrini, et al., 2020a). One particular Ganymede fluxtube crossing (on PJ30, 8 November, 2020), during which Juno was connected for the first time to the leading‐most Ganymede auroral spot, brought a set of in‐situ and remote sensing measurements consistent with what was expected during a TEB crossing (Hue et al., 2022). Unlike for Io and Ganymede, crossing through the fluxtube connected to the Europa footprint tail showed signs of electron distribution resulting at least in part from electrostatic acceleration processes (Allegrini et al., 2020).…”
Section: Introductionmentioning
confidence: 78%
“…Juno in‐situ instruments provided invaluable measurements of the particle distribution on the magnetic field lines connected to the satellite footprints and tails, such as measurements connected to Io (Clark et al., 2020; Szalay et al., 2018; Sulaiman et al., 2020, 2023; Szalay, Allegrini, et al., 2020b), Europa (Allegrini et al., 2020), and Ganymede (Hue et al., 2022; Louis et al., 2020; Szalay, Allegrini, et al., 2020a). Szalay, Allegrini, et al.…”
Section: Lead Anglesmentioning
confidence: 99%
“…These results have shed light on the various facets of the interaction including electron and proton acceleration (Szalay et al, 2018;2020a, 2020b, energetic particle dynamics (Paranicas et al, 2019;Clark et al, 2020), magnetic field fluctuations (Gershman et al, 2019), and cross-scale wave-particle interactions (Sulaiman et al, 2020). Although limited due to the relatively weaker interaction, field and particle observations connected to the orbits of Ganymede and Europa have also been reported (Allegrini et al, 2020;Szalay et al, 2020c;Hue et al, 2022). However, a study dedicated to how the Alfvénic Poynting fluxes are related to the electron energy fluxes, as well as estimating the field-aligned current densities of the Io-Jupiter interaction, remain essential pieces of the picture and will be the focus of this letter, where we analyze Io events during Juno's Prime Mission.…”
Section: Introductionmentioning
confidence: 86%